Vertical‐Space‐Limit Synthesis of Bifunctional Fe, N‐Codoped 2D Multilayer Graphene Electrocatalysts for Zn‐Air Battery. Issue 6 (10th April 2019) - Wang, Chen; Li, Zhongfang; Wang, Likai; Lu, Xuewei; Wang, Suwen; Niu, Xueliang
Abstract : Developing a green, cost‐efficient air‐cathode catalyst with high oxygen evolution and reduction reaction (OER/ORR) performance for rechargeable Zn‐air batteries (ZABs) has gained attention. Iron‐containing nitrogen‐doped graphene (Fe/N‐G) that contains Fe‐N x coordination sites is prepared by pyrolyzing the complex of iron ion and PANI sheets intercalated with the unique layer gaps of H‐montmorillonite nanoreactors. The transmission electron microscopy (TEM), X‐ray diffraction (XRD), and X‐ray photoelectron spectroscopy (XPS) analysis confirm that there are no crystalline materials, such as iron lattice, iron carbide, or iron nitride. The as‐prepared Fe/N‐G show a high electrocatalytic activity in ORR with a 4e − transfer process and the half‐wave potential of Fe/N‐G (0.877 V vs reversible hydrogen electrode—RHE), which is better than that of Pt/C in oxygen saturated 0.1 m KOH solution. In an acid electrolyte, the Fe/N‐G possesses a half‐wave potential similar to that of 20 wt% Pt/C. For OER, the Fe/N‐G exhibits the overpotential of 400 mV versus RHE at 10 mA cm −2 . However, the Fe/N‐G as the air‐cathode of the homemade rechargeable ZABs exhibits a high power density (156.8 mW cm −2 ) and an excellent long discharge–charge cycling stability (787 cycles) at 20 mA cm −2 . This work provides an inspiring guideline to prepare a high‐performance bifunctional air‐cathode for a rechargeable ZAB. Abstract : A bifunctional Fe, N‐codoped 2D multilayer graphene (Fe/N‐G) electrocatalyst possesses an excellent oxygen evolution and reduction reaction activity and durability owing to the spatial confinement of H‐MMT, which increases the content of active sites including in‐plane Fe‐Nx pyridinic N and pyrrolic N in the Fe/N‐G. This high‐performance bifunctional Fe/N‐G electrocatalyst has promising applications in the field of rechargeable Zn‐air batteries.